The benefits of mainstreaming environmental education in the school curriculum - Kimiti, Richard Peter; Cheruto, Kipkoech Lydia (Emerging Academy Resources, 2013)
The mismanagement and even over- exploitation of environment has been an area of concern globally in the last three decades. This is closely related to human activities such as mining, human settlement and agriculture. In retrospect, these effects are now being felt through drastic climatic changes, rising of the water basin and distinction of important plant and animal species. This catastrophy has been associated to inappropriate knowledge, ignorance and retributive attitudes towards environmental issues. The purpose of this study was therefore to investigate the benefits accrued through the mainstreaming of environmental education in the school curriculum. It was guided by one research objective, that is, to examine the benefits of mainstreaming themes of environmental education in the school curriculum. The significance of this study would be: to add more information to the present literature on benefits of mainstreaming environmental education in the school curriculum, to help curriculum developers in formulation of a syllabus that mainstreams environmental education in the school curriculum and to provide a feedback to the Kenyan community on the benefits of mainstreaming environmental education in the school curriculum. This study adopted a survey design. The findings of the study revealed that mainstreaming environmental education in the school curriculum equipped learners with the necessary knowledge and skills that is instrumental in preserving and conserving the environment. The study further revealed that the teaching of environmental education helped the learners to develop positive patterns of behaviour toward the environment. It was therefore concluded that the curriculum implementers should give more emphasis on teaching of environmental education at various levels as a method of promoting better management of the environment. Finally this study, recommends that: curriculum developers at the Kenya Institute of Education should ensure that topics on Environmental Education are integrated at all levels in the school curriculum and information on Environmental Education should be disseminated through other educational programmes such as adult literacy and other non-formal activities.
Keywords: Benefits; Curriculum; Education; Environment and Mainstreaming